Methaemoglobin and Malondialdehyde Levels of Human Erythrocytes Incubated with Acetylsalicylic Acid - Graham, Marika Louise; Chikezie, Paul Chidoka (Free Radicals and Antioxidants)
Background: MetHb and MDA are biomarkers for erythrocyte redox status and membrane lipid peroxidation, respectively. This present study aims to investigate the levels of human erythrocyte redox status and membrane lipid peroxidation indicators in the presence of ASA over time using in vitro models. Materials and Methods: The %MetHb was evaluated by measuring the absorbance of human erythrocyte suspension at λmax=630 nm and 540 nm. Human erythrocytes were incubated in 0.125 mg/mL, 0.25 mg/mL and 0.5 mg/mL ASA over a 6 hr incubation period. The human erythrocyte MDA concentration was measured using the TBARS assay. Results: The %MetHb of human erythrocytes following 3 hr of incubation with 0.125 mg/mL ASA gave a peak value of 2.70±1.36%, indicating a relative significant (p<0.05) increase of 45.16% compared with the control samples. Furthermore, an increase in the incubation time resulted in a decrease in erythrocyte %MetHb, although not to the levels observed at the beginning (t=0 hr) of incubation with ASA. Conversely, MDA concentration of human erythrocytes was 4.45±0.89 μM after 3 hr of incubation with 0.125 mg/mL ASA, showing a significant (p<0.05) decrease of 27.88%. Conclusion: The present study showed a negative correlation between %MetHb and MDA levels in human erythrocytes incubated with ASA over time, suggesting that the erythrocytes redox status did not specifically induce membrane lipid peroxidation.
Keywords: Acetylsalicylic Acid; Erythrocyte; Malondialdehyde; Methaemoglobin